2008
DOI: 10.1007/s00280-008-0713-y
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of aprepitant and dexamethasone in the prevention of chemotherapy-induced nausea and vomiting

Abstract: A pharmacokinetic model for aprepitant has been developed that incorporates body weight, age, ALT, BUN and aprepitant dose to predict the CL/F. The results of population pharmacokinetic analysis of dexamethasone support dose adjustment of dexamethasone in the case of co-administration with aprepitant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 22 publications
6
32
2
Order By: Relevance
“…Nakade et al also reported that body weight affected the oral clearance of aprepitant. 10) This inconsistency between the current study and their report on the contribution of body weight to the plasma pharmacokinetics of aprepitant is most likely due to the narrower range of the body weights in our study (40-85 kg) compared to their patients (33-93 kg). earlier studies with various doses of aprepitant indicated some nonlinearity in the disposition of aprepitant, reflecting saturation of metabolism and decreased clearance with an increasing dose.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…Nakade et al also reported that body weight affected the oral clearance of aprepitant. 10) This inconsistency between the current study and their report on the contribution of body weight to the plasma pharmacokinetics of aprepitant is most likely due to the narrower range of the body weights in our study (40-85 kg) compared to their patients (33-93 kg). earlier studies with various doses of aprepitant indicated some nonlinearity in the disposition of aprepitant, reflecting saturation of metabolism and decreased clearance with an increasing dose.…”
Section: Discussioncontrasting
confidence: 85%
“…Nakade et al reported that ALT affected the oral clearance of aprepitant, 10) although their study did not examine linear correlation. These enzyme activities are affected by not only hepatic function, 19) but also by the extent of liver fat accumulation, 20) insulin resistance, 20,21) inflammation, 22) and oxidative stress.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The final concentrations of the drugs during exposure were 100 nM, 10, 2 and 1 ”M for DEX, CDDP, 5-FU and RU-486, respectively. The concentrations of DEX, CDDP and 5-FU were set to mimic clinical conditions (7)(8)(9). To examine the inhibitory effects on DEX-induced Cys C secretion, CDDP, 5-FU and RU-486 were added to the culture medium containing DEX at the abovementioned concentrations for each drug.…”
Section: Methodsmentioning
confidence: 99%